AGE CONSTRAINTS AND SOURCE AREAS FOR THE PRECAMBRIAN TO CAMBRIAN STRATA OF THE SOUTHERN YENISEI RIDGE (REDKOLESNAYA AND OSTROVNOY FORMATIONS) - V. V. Marusin; B. B. Kochnev; G. A. Karlova; A. I. Proshenkin (Геодинамика и тектонофизика)
The Precambrian to Cambrian strata at the southwestern margin of the Siberian Platform are ubiquitously characterized by a gradual transition from red-colored alluvial and deltaic deposits to shallow-marine carbonates, reflecting a transgressive infill of the accommodation space of the foreland basin. However, a supposed synchronicity of the Early Precambrian marine transgressive events calls for verification by geochronological and bio- and chemostratigraphic dating. The herein-presented data on small skeletal fossils, trace fossils and variations in the carbon isotope composition of carbonates from the mixed carbonate-terrigenous succession (Redkolesnaya and Ostrovnoy formations) in the southern Yenisei ridge show that the base of the Cambrian Fortunian stage is placed within the Redkolesnaya formation. Age distribution of detrital zircons in the studied succession suggests the Siberian craton to be a major source of the clastic material in the foreland basin during the development of the Redkolesnaya formation. An increase in the amount of zircons derived from "non-Siberian" sources, located at the southwestern periphery of the paleocontinent at that time, in the coeval strata of the northern part of the southern Yenisei ridge, indicates a complex morphology of the paleobasin and considerable differentiation among the sources of clastic material therein.